Structure and Optical Properties of Nano PbS Thin Film Deposited by Pulse Laser Deposition - Yasmeen Z. Dawood; Suad M. Kadhim; Ayad Z. Mohammed (Engineering and Technology Journal, 2015)
The present work the structure properties of nano Lead sulfide PbS thin films were studied. Thin samples were prepared by pulse laser deposition and deposited on glass substrate at 1064nm wavelength with 800mj laser energy. The structure properties of films were determined by X-ray diffraction studied the effect of variation of substrate temperature on these properties. The films are adherent to the substrate and well crystallized according to the centered cubic structure with the preferential orientation (111) and (200). The minimum value of grain size was 16.5 nm when the film deposited of at 70 oC substrate temperature. The optical investigation showed that, depending on the substrate temperature have direct allowed transitions in the range 1.55–2.45 eV.